Exploring the roles of mitochondrial-associated microRNAs of head and neck cancer stem cells in drug resistance and tumor recurrence - Zhu, Xiaoning; Subha, Sethu Thakachy; Fong, Voon Hoong; Tan, Wee Lin; Cheah, Yoke Kqueen (Fundacao de Pesquisas Cientificas de Ribeirao Preto, 2024)
Head and neck cancer (HNC) is one of the most common cancers worldwide. The primary clinical issues in HNC are drug resistance and tumor recurrence attributed to the presence of cancer stem cells (CSCs). Dysfunction of mitochondria may prevent CSCs from apoptosis. MicroRNAs have been reported to be a potential target for diagnosis and treatment strategy in many types of cancers, including HNC. However, the roles of mitochondrial-associated miRNAs in head and neck cancer stem cells remain unclear. First, 18 mitochondrial-associated miRNAs of head and neck cancer stem cells were identified from the MitoCarta3.0 database, head and neck squamous cell carcinoma data in the TCGA database, and cancer stem cell surface markers of HNC by bioinformatic analysis. Then, the data mining determined let-7c-5p, the potential mitochondrial-associated miRNA of head and neck cancer stem cells related to drug resistance and tumor recurrence. Next, RT-qPCR verified the low expression of Let-7c-5p in head and neck cancer stem cells. After that, we further used bioinformatic analysis to predict that let-7c-5p might mainly target KRAS and BCL2L1 to regulate mitophagy and apoptosis pathways for keeping cancer stem cells alive. Hence, the treatment strategy based on let-7c-5p may provide novel solutions for drug resistance and recurrence in HNC.